The Core Promoter Is a Regulatory Hub for Developmental Gene Expression - Sloutskin, Anna; Shir-Shapira, Hila; Freiman, Richard N.; Juven-Gershon, Tamar (Frontiers in Cell and Developmental Biology, 2021)
The development of multicellular organisms and the uniqueness of each cell are achieved by distinct transcriptional programs. Multiple processes that regulate gene expression converge at the core promoter region, an 80bp region that directs accurate transcription initiation by RNA polymerase II (Pol II). In recent years, it has become apparent that the core promoter region is not a passive DNA component, but rather an active regulatory module of transcriptional programs. Distinct core promoter compositions were demonstrated to result in different transcriptional outputs. In this mini-review, we focus on the role of the core promoter, particularly its downstream region, as the regulatory hub for developmental genes. The downstream core promoter element (DPE) was implicated in the control of evolutionarily conserved developmental gene regulatory networks governing body plan in both the anterior-posterior and dorsal-ventral axes. Notably, the composition of the basal transcription machinery is not universal, but rather promoter-dependent, highlighting the importance of specialized transcription complexes and their core promoter target sequences as key hubs that drive embryonic development, differentiation and morphogenesis across metazoan species. The extent of transcriptional activation by a specific enhancer is dependent on its compatibility with the relevant core promoter. The core promoter content also regulates transcription burst size. Overall, while for many years it was thought that the specificity of gene expression is primarily determined by enhancers, it is now clear that the core promoter region comprises an important regulatory module in the intricate networks of developmental gene expression.